POLA KANDUNGAN PARASIT PADA TKUS-TIKUS DI KEBUN RAYA BOGOR - KADARSAN, S.; PURWANINGSIH, E.; HARTINI, S.; BUDIARTI, I.; SAIM, A. (Research Center for Biology-Indonesian Institute of Sciences, 1986)
S. KADARSAN, E. PURWANINGSIH, S. HARTINI, I.BUDIARTI & A. SAIM 1986. The pattern of parasite infestation on rats at the Bogor Botanical Garden.Berita Biologi 3(4): 173 - 177. Three species of rats namely Rattus exulans, R. r. diardi and R. tiomanicus inhabiting the Bogor Botanical Garden were investigated with respect to their ectoand endoparasite fauna.All three species were infested with Laelaps nutalli, Echinolaelaps echidninus (Acarina); Hoplopleura pacifica and Polyplax reclinata (Anoplura); Xenopsylla cheopis (Siphoriaptera);Hydatigera taeniaefortnis and Viktorokara sp.(Helminth).Additional parasites were Poecilochinis sp., Polyplax spinulosa and Beaveria sp.,a new and yet to be described Troglotrematid Trematode found only R.tiomanicus.The rate of infestation is in part dependent on the age and sex of the host which is seemingly associated with the mobility and food searching capability of the host Time may play an additional role as well.